Healthy Village House Program Outcomes in Panggreh Village, Jabon District - Maf’ula, Faima; Agustina, Isna Fitria (Indonesian Journal of Cultural and Community Development, 2024)
Background: This research explores the implementation of the Healthy Village Program, emphasizing local health initiatives' role in public health. Specific Background: It examines communication, resources, disposition, and bureaucratic structures within a particular village context. Knowledge Gap: There is limited analysis of these programs' effectiveness and community engagement in rural areas. Aims: The study aims to assess the program's impact on maternal and child health and its role in reducing stunting risks. Results: Findings reveal significant improvements in community health practices and increased resident participation. Novelty: This research provides new empirical evidence on the effectiveness of local health programs and their bureaucratic structures. Implications: It highlights the necessity for organized bureaucratic frameworks to sustain health initiatives and improve villagers' quality of life, supporting Edward III's theory on policy implementation and bureaucratic structures. Highlights : Local health initiatives enhance community participation in health maintenance. Effective bureaucratic structures are essential for sustaining health programs. The study provides empirical evidence on the impact of rural health interventions. Keywords: Healthy Village Program, maternal health, community engagement, stunting reduction, bureaucratic structure